2018
DOI: 10.1155/2018/8316212
|View full text |Cite
|
Sign up to set email alerts
|

Risk for ASD in Preterm Infants: A Three-Year Follow-Up Study

Abstract: Background The aim of this study was to examine the long-term risk for autism spectrum disorders (ASD) in individuals who are born preterm and full-term using both observational instruments and parental reports. Neonatal risk factors and developmental characteristics associated with ASD risk were also examined. Method Participants included 110 preterm children (born at a gestational age of ≤ 34 weeks) and 39 full-term children assessed at ages 18, 24, and 36 months. The Autism Diagnostic Observation Schedule, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
(54 reference statements)
2
11
1
Order By: Relevance
“…The inconsistency of findings regarding child development after preterm birth in the current study with previous literature may be attributed to the young age of the children in this sample (22–34 months) as compared to previous studies that had included children between 3 and 18 years of age ( 62 , 65 , 66 ). As previous research has not yet included children within toddler age with a diagnosis of autism, it is possible that differences in development may not become apparent until the child reaches an older age.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…The inconsistency of findings regarding child development after preterm birth in the current study with previous literature may be attributed to the young age of the children in this sample (22–34 months) as compared to previous studies that had included children between 3 and 18 years of age ( 62 , 65 , 66 ). As previous research has not yet included children within toddler age with a diagnosis of autism, it is possible that differences in development may not become apparent until the child reaches an older age.…”
Section: Discussioncontrasting
confidence: 96%
“…In the current study using a sample of 2-year-old children, these differences were not identified. Similar results were found for children born preterm who were identified at “high likelihood” for an autism diagnosis using screening tools ( 28 , 65 ). Further, previous findings using typically developing samples have suggested that children born preterm have substantially delayed development when compared to children born full-term ( 20 , 84 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Preterm children are at particular risk of presenting a broad range of developmental di culties, such as language delay, communication and social disturbances, as well as ASD (2)(3)(4). Both children with ASD and preterm children are more likely to exhibit internalizing and externalizing di culties early in life (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%